2009
DOI: 10.3758/app.71.8.1793
|View full text |Cite
|
Sign up to set email alerts
|

Hiding and finding: The relationship between visual concealment and visual search

Abstract: Souther, 1985). The second stimulus set, the affective-face set, which included three different affective faces, has been 1793© As an initial step toward developing a theory of visual concealment, we assessed whether people would use factors known to influence visual search difficulty when the degree of concealment of objects among distractors was varied. In Experiment 1, participants arranged search objects (shapes, emotional faces, and graphemes) to create displays in which the targets were in plain sight bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 52 publications
(59 reference statements)
4
16
0
Order By: Relevance
“…The placing of easy targets in corner positions of the display and hard targets more centrally converges with the notion that edges are a salient feature that supports pop-out in a variety of domains (e.g., texture, motion, disparity), whereas a target is well camouflaged when surrounded by like items. Our finding that participants have accurate and natural intuitions of these facts dovetails with Smilek et al (2009).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The placing of easy targets in corner positions of the display and hard targets more centrally converges with the notion that edges are a salient feature that supports pop-out in a variety of domains (e.g., texture, motion, disparity), whereas a target is well camouflaged when surrounded by like items. Our finding that participants have accurate and natural intuitions of these facts dovetails with Smilek et al (2009).…”
Section: Discussionmentioning
confidence: 61%
“…If changes in the visual environment and/or a participant's conceptualization of the hider or finder (friend or foe) has the same impact on search and concealment behaviour, then the evidence will be that the two behaviours reflect the same underlying processes (Smilek et al 2009). A significant change in search and concealment behaviour would suggest a very different conclusion.…”
Section: Investigated Whether Individuals'mentioning
confidence: 99%
“…Very little work has explored the former aspect, though what has been done suggests that the factors that facilitate search dovetail with the factors that facilitate action. For example, Smilek, Weinheimer, Kwan, Reynolds, and Kingstone (2009) have shown that participants asked to arrange search items to make search easy tend to centralize targets, group similar items, and arrange distractors in regular arrays. Similarly, Anderson, Foulsham, Nasiopoulos, Chapman, and Kingstone (2014) report that individuals hiding an item for a friend (in contrast to hiding an item adversarially) tended to select a nearby, easy-to-reach location.…”
Section: Search and Memorymentioning
confidence: 99%
“…Studies of human adult search behaviors have generally focused on visual search for a target object among distractors in two-dimensional displays of artificial and natural scenes (e.g., [4][5]), or the concealment of objects within a visual display [6]. One recent study [7] investigated strategies used by people to search for a single object in a complex three-dimensional virtual maze.…”
Section: Introductionmentioning
confidence: 99%